Improving the selection of MPRs in OLSR protocol: a survey of methods and techniques - Omar Barki; Zouhair Guennoun; Adnane Addaim (Institute of Advanced Engineering and Science, 2020)
Multi Point Relays (MPRs) are those nodes that are calculated and determined by the Optimized Link State Routing protocol (OLSR) in order to minimize and avoid overload inside the Mobile Ad hoc Network (MANET). In this paper, we will present a synthetic study of many techniques and methods for calculating and selecting the MPR nodes using a set of criteria namely energy, mobility, bandwidth, the quality of links, etc. The result of this study shows that most techniques consider a limited number of metrics for selecting the MPR nodes and therefore they are insufficient to allow the OLSR protocol to be quite complete and efficient because several metrics can occur at the same time in the real execution environment.